Spectro-polarimetric observations at the NVST: I. instrumental polarization calibration and primary measurements - Hou, Jun-Feng; Xu, Zhi; Yuan, Shu; Chen, Yu-Chao; Peng, Jian-Guo; Wang, Dong-Guang; Xu, Jun; Deng, Yuan-Yong; Jin, Zhen-Yu; Ji, Kai-Fan; Liu, Zhong (Research in astronomy and astrophysics, 2020)
This paper is devoted to the primary spectro-polarimetric observation performed at the New Vacuum Solar Telescope (NVST) of China since 2017, and our aim is to precisely evaluate the real polarimetric accuracy and sensitivity of this polarimetry by using full Stokes spectro-polarimetric observations of the photospheric line Fe I 532.4 nm. In the work, we briefly describe the salient characteristic of the NVST as a polarimeter in terms of technology and then characterize its instrumental polarization based on the operation in 2017 and 2019. It is verified that the calibration method utilizing the instrumental polarization calibration unit (ICU) is stable and credible. The calibration accuracy can reach up to 3 × 10−3. Based on the scientific observation of NOAA Active Region 12645 on 2017 April 5, we estimate that the residual cross-talk from Stokes I to Stokes Q, U and V, after the instrumental polarization calibration, is about 4 × 10−3 on average, which is consistent with the calibration accuracy and close to the photon noise. The polarimetric sensitivity (i.e., the detection limit) for polarized light is of the order of 10−3 with an integration time over 20 s. Slow modulation rate is indeed an issue for the present system. The present NVST polarimeter is expected to be integrated with a high-order adaptive optics system and a field scanner to realize 2D vector magnetic field measurements in the following instrumentation update.